Adam Smith als Rechtstheoretiker - Petersen, Jens (De Gruyter, 2017)
Adam Smith was not only a founder of modern political economics but also a moral philosopher, who gave a lecture series titled Lectures on Jurisprudence, now preserved only in lecture notes. He was unable to realize his plans to create a comprehensive theory of the law and burned all drafts of the work. However, relevant sections of his major works enable the reconstruction of a substantial portion of his ideas in the area of legal theory.